ANALISIS PENERAPAN VARIABEL COSTING SEBAGAI ALAT UNTUK MENGHITUNG HARGA POKOK PRODUKSI PADA AKSAN BAKERY DI MANADO - Darise, Tety; Saerang, David Paul Elia; Wangkar, Anneke (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
Determining the cost of goods sold is right becomes one factor supporting the success of a company in achieving its goals , the cost of production has an important role in a company , due to the determination of the cost of goods sold , the company could easily determine the selling price , and the targeted profit also clear. This research was conducted at a company manufacturing in Manado . This study aimed to analyze the application of variable costing in Aksan Bakery in Manado. Data analysis method used is descriptive analysis . The data used is qualitative data , the data is presented in a descriptive or shape description and quantitative data , the data presented in the form of numbers. The research findings show that the application of variable costing method can be used as a tool to calculate the cost of production in the AksanÂ  Bakery. It can be seen from a comparative analysis of the cost of goods sold according to variable costing lower than the production cost price calculation method used Aksan Bakery. By using the full costing method used by companies the cost of goods sold Rp . 1.191.956 .000 while according to the variable cost of production costing Rp . 1.033.560.000. The main difference between full costing calculation method used by the company with variable costing method lies in the treatment of factory overhead costs .Keywords : cost of goods sold, variabel costing